Modification and Actuator Minimization of the Hip Leg Joint in a Bipedal Robot: A Proposed Design - Nirmalya Tripathi (Institute of Advanced Engineering and Science, 2015)
In recent times, there have been numeric applications of Biped Robots. In this paper, a proposed upper leg hip design of a biped was developed taking cost reduction and optimization as factors for consideration. The proposed system introduces a novel method which consists of a vibration reduction (VR) DC stepper motor, microcontroller, microprocessor and gearing arrangement. The program in the microprocessor is so designed that it gives a fixed number of cycles/steps to the VR DC stepper motor in clockwise and thereafter in anti-clockwise direction. This turning movement can then be transmitted to the gearing system which precisely moves one upper leg when the VR DC stepper motor moves in clockwise direction, while the other upper leg remains static, and vice-versa. It has been observed that this new proposed system may reduce the cost overhead, weight and the energy consumption incurred by working on a single VR DC stepper motor while conventionally two stepper motors are used to give the motion of the two upper legs in a biped.